Association of Platelet Volume Indices with HbA1c Levels in Type 2 Diabetes Mellitus and Non-diabetic Individuals: A Cross-sectional Analytical Study - Prabhjot Kaur; Anshul Gupta; Nidhi Bansal; Tamanna Kalra; Navtej Singh; Kuldeep Singh (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Platelets play a significant role in the pathophysiology of diabetes-related vascular complications. Chronic hyperglycaemia contributes to endothelial dysfunction, oxidative stress and increased platelet activation, which all together promote a prothrombotic state. Platelet Volume Indices (PVI), including Mean Platelet Volume (MPV) and Platelet Distribution Width (PDW), are considered markers of platelet activation and reactivity, early estimation of which can help in early detection of diabetes related complications. Aim: To study association of PVI (MPV and PDW) with HbA1c in diabetes mellitus type 2 patients and non diabetics. Materials and Methods: This cross-sectional comparative study was conducted in the Department of Pathology and the Department of Immunohaematology and blood transfusion in a tertiary care hospital of Adesh Institute of Medical Sciences and Research, Bathinda, Punjab, India on 300 subjects: 200 Type 2 Diabetes Mellitus (T2DM) patients and 100 healthy controls (blood donors) from 1st November 2018 to 31st January 2020. Diabetics were sub-divided based on HbA1c: Group A (HbA1c ≥7.5%), Group B (HbA1c 6.5-7.4%) and Group C was of controls (HbA1c ≤6.4%). Platelet indices (MPV and PDW) and HbA1c were measured and statistically analysed using Statistical Packages of Social Sciences (SPSS) version 26.0 Quantitative variables were expressed as mean±standard deviation. Chi-square test, MannWhitney U/Z-score test and Pearson’s/Spearman correlation were applied considering p-value